The Controversy Surrounding Rev. Włodzimierz Kirchner’s Brochure [Challenging Poverty in Bałuty] - Samborska-Kukuć, Dorota (Czytanie Literatury. Łódzkie Studia Literaturoznawcze, 2019)
Włodzimierz Kirchner (1875-1970) – former priest, activist in the Łódź and Warsaw districts of the Christian Charity Association, he supported the efforts of the organisation by publishing articles on philanthropy. He was a proponent of the so-called ‘enlightened philanthropy’, i.e. he argued that social support cannot be of a spontaneous and chaotic character, but, rather, it should be controlled and monitored so that unemployment can be prevented. To justify his theses, the main of which was a conviction that giving alms was a waste of money and a tool spreading demoralisation, he conducted an analysis of dysfunctional communities, e.g. Bałuty (near Łódź back then). He depicted the inhabitants of the area (serving as a synecdoche of the dysfunctional communities throughout Poland) as a group of pretenders and impostors hustling potential benefactors by using a theatricalisation of behaviours which evoked empathy. He collected and published his conclusions in the brochure titled Walka z nędzą na Bałutach, which – due to its controversial recommendations of emotional restraint and the application of the method of control and monitoring – stirred aversion among various groups of intellectuals. Kirchner was accused of blind support of doctrines and extreme aestheticism, while the leftist press accused him of hypocrisy typical of the clergy.